The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1523/jneurosci.2070-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Surface Actin Binds Plasminogen and Modulates Neurotransmitter Release from Catecholaminergic Cells

Abstract: An emerging area of research has documented a novel role for the plasminogen activation system in the regulation of neurotransmitter release. Prohormones, secreted by cells within the sympathoadrenal system, are processed by plasmin to bioactive peptides that feed back to inhibit secretagogue-stimulated release. Catecholaminergic cells of the sympathoadrenal system are prototypic prohormone-secreting cells. Processing of prohormones by plasmin is enhanced in the presence of catecholaminergic cells, and the enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 66 publications
1
61
0
Order By: Relevance
“…For example, treatment of monocytoid cells with carboxypeptidase B (CpB), which removes carboxyl-terminal lysines, leads to a decrease of 64% for plasminogen binding and >95% for plasminogen activation ( 39 ). On catecholaminergic cells, binding of plasminogen decreased following CpB treatment by ‫ف‬ 70%, whereas a decrease of 90% was observed for plasminogen activation ( 40 ). In another study, binding of plasminogen to human umbilical vein endothelial cells (HUVECs) was also inhibited by -aminocaproic acid ( -ACA), a lysine analog, by 70-80% ( 29 ).…”
Section: Plasminogen Activation Assaymentioning
confidence: 99%
“…For example, treatment of monocytoid cells with carboxypeptidase B (CpB), which removes carboxyl-terminal lysines, leads to a decrease of 64% for plasminogen binding and >95% for plasminogen activation ( 39 ). On catecholaminergic cells, binding of plasminogen decreased following CpB treatment by ‫ف‬ 70%, whereas a decrease of 90% was observed for plasminogen activation ( 40 ). In another study, binding of plasminogen to human umbilical vein endothelial cells (HUVECs) was also inhibited by -aminocaproic acid ( -ACA), a lysine analog, by 70-80% ( 29 ).…”
Section: Plasminogen Activation Assaymentioning
confidence: 99%
“…g-actin influences cell growth and plays a role in the readout of genetic information (Fojo, 2006). Miles et al (2006) reported on plasminogen-binding proteins identified as rat b/g-actin on cell surfaces that, upon binding, increased prohormone processing, leading to inhibition of catecholamine release. Desmin plays a role in the structural as well as functional interaction of mitochondria and the cytoskeleton (Capetanaki, 2002) and is typically associated with mitochondrial function in muscle cells (Fountoulakis et al, 2005).…”
Section: The Study Ran From September 2006 To April 2007 and Was Apprmentioning
confidence: 99%
“…[91][92][93][94][95][96][97] In addition, PavB and PfbA, as well as PavA, promote the attachment of the pneumococcus to fibronectin, a component of the extracellular matrix.…”
Section: Pneumococcal Adherence and Virulence Factors A And B (Pav A/b)mentioning
confidence: 99%